Basilar Artery Vasospasm as a Cause of Post-Operative Cerebellar Mutism Syndrome. (10th February 2022) - Deghedy, Marwa; Pizer, Barry; Kumar, Ram; Mallucci, Conor; Avula, Shivaram
Abstract : Post-operative cerebellar mutism syndrome (CMS), also known as posterior fossa syndrome (PFS), is a well-recognized and frequent complication of surgery for posterior fossa tumours in children and young people. Its incidence varies between 8 and 31%, and the pathophysiological mechanisms of delayed onset and resolution of cerebellar mutism are not clear, but axonal damage, oedema, and perfusion defects may be involved. Magnetic resonance imaging has failed to reveal a universal anatomical substrate or a single definite mechanism of injury. We present a case of 16-year-old boy who developed CMS three days after resection of a medulloblastoma, a primary fourth ventricular tumour. Early post-operative imaging showed bleeding in the posterior fossa which required evacuation. CT angiography seven days after surgery demonstrated basilar artery vasospasm. Magnetic resonance brain angiography confirmed persistent narrowing of a segment of the basilar artery closely related to a left cerebellopontine (CP) angle peri-operative haematoma. The patient was treated with nimodipine and hypervolemia. The patient started vocalisation without speech five days later with reversal of radiological lesions. Further recovery of post-operative neurological deficits occurred over a protracted period of several months. This case represents a rare cause of post-operative CMS, with rapid initial recovery that occurred after specific treatment directed at the cause. To our knowledge, this is the first reported case showing mutism associated with basilar artery vasospasm with imaging evidence. This case may suggest the need to undertake urgent vascular imaging in selected cases of post-operative CMS.